Sources of Holocaust insight : learning and teaching about the genocide - Roth, John K. (2020)
Sources of Holocaust Insight maps the odyssey of an American Christian philosopher who has studied, written, and taught about the Holocaust for more than fifty years. What findings result from John Roth's journey; what moods pervade it? How have events and experiences, scholars and students, texts and testimonies–especially the questions they raise–affected Roth's Holocaust studies and guided his efforts to heed the biblical proverb: "Whatever else you get, get insight?" More sources than Roth can acknowledge have informed his encounters with the Holocaust. But particular persons–among them Elie Wiesel, Raul Hilberg, Primo Levi, and Albert Camus–loom especially large. Revisiting Roth's sources of Holocaust insight, this book does so not only to pay tribute to them but also to show how the ethical, philosophical, and religious reverberations of the Holocaust confer and encourage responsibility for human well-being in the twenty-first century. Seeing differently, seeing better–sound learning and teaching about the Holocaust aim for what may be the most important Holocaust insight of all: Take nothing good for granted.